Oral Unsaturated Fat Load Impairs Postprandial Systemic Inflammation in Primary Hypercholesterolemia Patients - Collado, Aida; Domingo, Elena; Marques, Patrice; Perello, Eva; Martínez-Hervás, Sergio; Piqueras, Laura; Ascaso, Juan F.; Real, José T.; Sanz, Maria-Jesus (Frontiers in Pharmacology, 2021)
Context: Primary hypercholesterolemia (PH) is a lipid disorder characterized by elevated levels of cholesterol and low-density lipoprotein (LDL). Low-grade systemic inflammation is associated with PH, which might explain the higher incidence of cardiovascular diseases in this setting. Objective: To evaluate the effect of an oral unsaturated fat load (OUFL) on different immune parameters and functional consequences in patients with PH in postprandial state. Design: A commercial liquid preparation of long-chain triglycerides (Supracal®; ω6/ω3 ratio >20/1, OUFL) was administered to 20 patients and 10 age-matched controls. Whole blood was collected before (fasting state) and 4 hours after administration (postprandial state). Flow cytometry was employed to determine platelet and leukocyte activation, and the levels of circulating platelet-leukocyte aggregates. Soluble markers were determined by ELISA, and the parallel-plate flow chamber was employed to study leukocyte adhesion to the dysfunctional arterial endothelium. Results: The PH group had a lower percentage of activated platelets and circulating type 1 monocytes, and blunted neutrophil activation after the OUFL, accompanied by a significant increase in the percentage of regulatory T lymphocytes. In this group, the OUFL led to a significant impairment of leukocyte adhesion to the dysfunctional (tumor necrosis factor α [TNFα]-stimulated) endothelium and reduced the plasma levels of soluble P-selectin, platelet factor-4 (PF-4)/CXCL4, CXCL8, CCL2, CCL5, and TNFα. Conclusions: The OUFL has a beneficial impact on the pro-thrombotic and pro-inflammatory state of PH patients and might be a promising macronutrient approach to dampen the systemic inflammation associated with PH and the development of further cardiovascular events.